Regulation of the macrolide resistance ABC-F translation factor MsrD - Corentin R. Fostier; Farès Ousalem; Elodie C. Leroy; Saravuth Ngo; Heddy Soufari; C. Axel Innis; Yaser Hashem; Grégory Boël (Nature Communications, 2023)
Abstract Antibiotic resistance ABC-Fs (ARE ABC-Fs) are translation factors that provide resistance against clinically important ribosome-targeting antibiotics which are proliferating among pathogens. Here, we combine genetic and structural approaches to determine the regulation of streptococcal ARE ABC-F gene msrD in response to macrolide exposure. We show that binding of cladinose-containing macrolides to the ribosome prompts insertion of the leader peptide MsrDL into a crevice of the ribosomal exit tunnel, which is conserved throughout bacteria and eukaryotes. This leads to a local rearrangement of the 23 S rRNA that prevents peptide bond formation and accommodation of release factors. The stalled ribosome obstructs the formation of a Rho-independent terminator structure that prevents msrD transcriptional attenuation. Erythromycin induction of msrD expression via MsrDL, is suppressed by ectopic expression of mrsD, but not by mutants which do not provide antibiotic resistance, showing correlation between MsrD function in antibiotic resistance and its action on this stalled complex.